Southeast Asian affairs 2008 - Abinales, Patricio N.; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2008)
Contains contributions by experts that discuss the significant issues and events of the year in each of the Southeast Asian nations and the region as a whole.
The Philippines: weak state, resilient President Patricio N. Abinales.
Imprint varies.
Fi-8633g donated by Prof. Patricio BN Abinales & Donna Amoroso, Center for Southeast Asian Studies, Kyoto University, Japan.
Keywords: Southeast Asia -- Economic conditions; Southeast Asia -- Economic policy; Southeast Asia -- Politics and government; Southeast Asia -- Periodicals